Cover Feature: The Pivotal Role of Boron in Improving the Azo Dye Degradation of Glassy Fe‐based Catalysts (ChemCatChem 3/2020). Issue 3 (21st January 2020) - Xie, Shenghui; Xie, Yuelin; Kruzic, Jamie J.; Gu, Kunming; Yang, Haipeng; Deng, Yuanming; Zeng, Xierong
Abstract : The Cover Feature shows the process and mechanism of the highly efficient degradation of azo dyes by Fe‐based catalytic characterized by three different galvanic cells. In their Full Paper, Shenghui Xie et al. describe how the electrode potential difference between the Fe‐rich cluster and Fe‐poor cluster in metal glass ensures a galvanic cell between them, defined here as a type 1 galvanic cell, which promote the Fe atoms in Fe‐rich clusters to lose electrons and promote the degradation reaction. Type 2 galvanic cells form between the ex‐added boron particle and Fe‐based metallic glass matrix, promoting the electrons loss in metallic glass and therefore accelerate the degradation. Type 3 galvanic cells can be generated between Fe and Fe‐B based compounds in the crystalline alloys through from annealing the metallic glass. Unexpectedly, it is the intermetallics (such as Fe2 B, FeB and Fe5 SiB2 ), not Fe, that denote electrons to promote degradation. The natural degradation of azo dyes is very slow. After introducing three different galvanic cells, the azo dyes are broken into small molecules rapidly and the water becomes clear. More information can be found in the Full Paper by Shenghui Xie et al. on page 750 in Issue 3, 2020 (DOI: 10.1002/cctc.201901623 ).